Effect of MLC901 on Red Cell Distribution Width (RDW) in Acute Ischemic Stroke: Literature Review - Ilham, M. Arya Rifqi; Hunaifi, Ilsa; Dirja, Bayu Tirta (Jurnal Biologi Tropis, 2024)
Acute ischemic stroke is an acute episode of neurological dysfunction caused by focal infarction or damage that persists for ≥24 hours in the brain, spine, and retinal. Stroke is the second highest cause of death worldwide. The total prevalence of stroke continues to increase in the world and in Indonesia. However, stroke treatment is still less effective, so adjuvant therapy needs to be developed; one of them is MLC901. However, this therapy still needs to be studied further regarding its effect on acute ischemic stroke and the biomarkers used as the prognostic factors, such as red cell distribution width (RDW). This paper aims to determine the effect of MLC901 therapy on RDW values in acute ischemic stroke by analyzing various previous studies from different databases as a reference. Increased RDW values are associated with poor outcomes of acute ischemic stroke. MLC901 was shown to have neuroprotective and neurorestorative abilities in neurons that are under stress due to ischemia. MLC901 also can reduce inflammatory responses, reduce oxidative stress, and increase erythropoietin (EPO) production. So, administration of adjuvant MLC901 therapy can reduce RDW values and improve neurological outcomes in acute ischemic stroke.